Rekonstruksi Hukum Ekonomi Syariah atas Praktik Sewa Ganda dan Sengketa Lahan Garam di Pamekasan - Linda Sari, Mailatun (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The dual leasing practice of salt lands in Pamekasan has become a chronic source of social and economic conflict among farmers. This study aims to analyze the insufficiency of Islamic Economic Law, particularly fiqh al-ijarah (lease jurisprudence), in addressing such disputes and to formulate a contextual and just reconstruction model of Islamic Economic Law (HES). The research employs a qualitative method with an empirical juridical approach. The findings reveal that dual leasing practices are normatively contradictory to HES as they contain elements of gharar (uncertainty) and tadlis (deception). Furthermore, the conventional fiqh al-ijarah framework has proven ineffective in practice due to its procedural and individualistic nature, which fails to accommodate communal social realities such as the lack of formal documentation and the dominance of customary law (‘urf) and local mediators. In conclusion, this study proposes a preventive-mediative hybrid model that shifts the focus from contractual procedures to the substance of maqasid al-shari‘ah, particularly the protection of rights and property, by integrating valid ‘urf through two pillars: a preventive pillar in the form of simplified lease documentation, and a mediative pillar through the institutionalization of local mediators as the first layer of dispute resolution. This model enables Islamic Economic Law to function as a living law that is contextual, adaptive, and just for salt-farming communities in Pamekasan.